Approximategeneralized Jensen typemappings in proper Lie CQ*-algebras (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In this paper, we investigate the stability problems for proper Lie derivations associated to the generalized Jensen typefunctional equation in a proper Lie CQ*-algebra.